2015
DOI: 10.1002/jcph.627
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1 genotype‐dependent dose adjustment of belinostat in patients with advanced cancers using population pharmacokinetic modeling and simulation

Abstract: Belinostat is a second-generation zinc-binding histone deacetylase inhibitor that is approved for peripheral T-cell lymphoma and is currently being studied in small cell lung cancer and other advanced carcinomas as a 48-hour continuous intravenous infusion. Belinostat is predominantly metabolized by UGT1A1, which is polymorphic. Preliminary analyses revealed a difference in belinostat clearance based on UGT1A1 genotype. A 2-compartment population pharmacokinetic (PK) model was developed and validated that inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Goey et al demonstrated that patients with an IM status for UGT1A1 (i.e., greater belinostat exposure) had greater incidence of grade 3 (platelet count between 25,000–50,000/µL) or grade 4 (<25,000/µL) thrombocytopenia compared to NM when receiving the belinostat, cisplatin, and etoposide combinanation [6]. This was consistent with IMs having a slower belinostat clearance and thus the recommendation of a 33% dose reduction for IMs based on PPK modelling and simulation when giving belinostat as a 48-h IV infusion [5]. …”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Goey et al demonstrated that patients with an IM status for UGT1A1 (i.e., greater belinostat exposure) had greater incidence of grade 3 (platelet count between 25,000–50,000/µL) or grade 4 (<25,000/µL) thrombocytopenia compared to NM when receiving the belinostat, cisplatin, and etoposide combinanation [6]. This was consistent with IMs having a slower belinostat clearance and thus the recommendation of a 33% dose reduction for IMs based on PPK modelling and simulation when giving belinostat as a 48-h IV infusion [5]. …”
Section: Discussionmentioning
confidence: 69%
“…Patients categorised as IM not only had slower belinostat plasma clearance [5, 6], but also tented to have a lower platelet nadir vs NM [41,800 ( n = 18) vs 70,400 ( n = 5)] count/µL; p = 0.053 (Mann-Whiteney); Supplemental Figure S2] that occurred roughly 6–7 days after cessation of belinostat. Based on this observation that slower belinostat clearance induced greater platelets decrease, coupled with an overall decrease in platelets with increasing belinostat concentration (Supplemental Figure S3), a semi-mechanistic myelosuppression PD model that included a rate constant between the proliferating and first maturation compartment ( k PT ) was added onto the original PPK model [5]. This differed from comparable models that used the same rate constant for this process as well as the inter-maturation compartment transit rate constant [ k TR ; calculated by mean transit time (MTT) = 4/ k TR , with MTT as an estimable parameter], which was assumed equivalent to k DEG and k PROL at steady state [7, 8, 15].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations